First proof-of-principle of inorganic perovskites clinical radiotherapy dosimeters - Mara Bruzzi; Cinzia Talamonti; Nicola Calisi; Stefano Caporali; Anna Vinattieri (APL Materials, 2019)
Inorganic CsPbBr3 perovskite devices have been manufactured and tested as dosimeters under both conventional and Intensity Modulated Radiotherapy (IMRT) X-ray beams. Samples showed a very good linear dependence of the collected charge/current on dose/dose rates in the range of 0.1–5.0 Gy/0.1–4.0 Gy/min of interest for clinical applications. A device sensitivity of about 70 nC/Gy mm3 compares favorably with other solid-state dosimeters. The first verification of an IMRT dose profile of a prostate cancer treatment, performed by moving the perovskite device on a 10 cm-long profile with a 0.5 mm pitch, showed agreement within 5% with the dose distribution required by the treatment planning system.